2017
DOI: 10.1007/s13197-017-2928-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of probiotic potential of Bacillus species isolated from a traditional brine pickle

Abstract: Fermented foods are known for their potential as main source of probiotics. The present study aimed at investigating the probiotic properties of bacteria isolated from fermented mango pickle. Non-hemolytic fermenting microbiota isolated from mango pickle was screened in vitro for their basic probiotic properties such as acid tolerance, bile salt, lysozyme and salt tolerance. They were also tested for their beneficial characters like cholesterol removal, bacterial adhesion to hydrocarbons, auto-aggregation, ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 30 publications
3
18
0
Order By: Relevance
“…The novel isolates could tolerate the intestinal pH, and the results are in line with other previous Bacillus probiotics (Ragul et al . ) and relatively higher than some Lactobacillus spp. (Wang et al .…”
Section: Discussionmentioning
confidence: 86%
“…The novel isolates could tolerate the intestinal pH, and the results are in line with other previous Bacillus probiotics (Ragul et al . ) and relatively higher than some Lactobacillus spp. (Wang et al .…”
Section: Discussionmentioning
confidence: 86%
“…The highest cholesterol removal rates were found over 90% at 6 h in B. licheniformis N17-02 and 18 h in P. chibensis Y13-51, respectively. Compared with three Lactobacillus strains, the removal rates were relatively higher in five isolates from Bacillales, ranging from 27.18% to 93.94%, which were higher than the removal rate 12.82-70.89% reported previously in Bacillus strains isolated from fermented vegetables [46]. To test whether bile salt could boost the relatively lower removal rate in Lactobacillus strains N15-22, X16-68 and X16-69, GDCA and TDCA were added.…”
Section: Cholesterol-lowering Potentialmentioning
confidence: 89%
“…Moreover, Sirichoat et al, (2020) showed sensitivity of lactobacillus strains to Steptomycin; while, these strains were resistant against Gentamycin, Vancomycin, Ampicillin and Tetracyclin. Ragul et al, (2017). However, the inhibitory effects of Lactobacillus rhamnosus strain against the S. aureus was found to be insignificant.…”
Section: Resultsmentioning
confidence: 93%